Corporate and project finance modeling : theory and practice - Bodmer, E. (Edward) (Hoboken, New Jersey : Wiley, 2014)
A clear and comprehensive guide to financial modeling and valuation with extensive case studies and practice exercises Corporate and Project Finance Modeling takes a clear, coherent approach to a complex and technical topic. Written by a globally-recognized financial and economic consultant, this book provides a thorough explanation of financial modeling and analysis while describing the practical application of newly-developed techniques. Theoretical discussion, case studies and step-by-step guides allow readers to master many difficult modeling problems and also explain how to build highly.
Structuring a Time Line to Measure History, Explicit Periods, and Terminal Periods in Corporate Models and Risk Phases in Project Finance ModelsComputing Start of Period and End of Period Dates; TRUE and FALSE Switches in Modeling Time Periods; Computing the Age of a Project in Years on a Monthly, Quarterly, or Semiannual Basis; The Magic of a HISTORIC Switch in a Corporate Model; Transferring Data from a Corporate Model to an Acquisition Model Using MATCH and INDEX Functions; Chapter 8: Projecting Revenues, Expenses, and Capital Expenditures to Derive Pretax Cash Flow; Transparent Calculations of Pretax Cash Flow
Description based on print version record and CIP data provided by publisher.
Keywords: Valuation -- Mathematical models; Finance -- Mathematical models; Financial risk -- Mathematical models; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Valuation -- Mathematical models; Electronic books; Electronic books